SAT0211 Reliability, Validity, and Sensitivity to Change of The Duruoz Hand Index in Systemic Sclerosis. (15th July 2016) - Gherghe, A.M.; Gyorfi, H.; Capota, R.; Matei, A.; Oneata, R.; Milicescu, M.; Macovei, L.; Sasu, M.; Bojinca, M.; Stoica, V.; Mihai, C.
Abstract : Background: Hand involvement is observed in almost all patients with Systemic Sclerosis (SSc), and is due to skin and tendon fibrosis, arthritis and microvascular impairment, sometimes complicated with digital ulcers (DUs). Objectives: The Duruoz's Hand Index (DHI) (or Cochin hand functional disability scale), is a reliable tool for hand function assessment and can be used in diseases like rheumatoid arthritis and SSc. The purpose of this study was to assess the reliability, validity and sensitivity to change of the DHI in SSc patients. Methods: 66 patients with SSc according to the 2013 ACR/EULAR criteria, examined in our EUSTAR center from 1.10.2014 to 31.12.2015 were included. Patients completed the DHI, the Scleroderma Health Assessment Questionnaire (SHAQ) questionnaires and the Hand Mobility in Scleroderma (HAMIS) test. Three anthropometric measures to assess finger range of motion were also measured: the finger extension (FE), finger-to-palm distance (FTP) and Δ FTP (FE - FTP). Step 1: In 38 patients the test-retest reliability, using intra-class correlation coefficients (ICC), and the internal consistency (Cronbach's alpha test) were examined. Step 2: In all 66 patients, the criterion validity by correlation coefficients with SHAQ, HAMIS and the anthropometric measures, and the discriminative capacity between different subsets of patients were examined. Step 3: 27 consecutive patients had a second evaluation at an interval of (mean±SD) 9.3±2.3 months; among them, only 4 patients had progressive early diffuse SSc. Sensitivity to change was assessed in these patients using the effect size (ES) (Cohen's d) and the standardized response mean (SRM). Results: The study included 59 females/7 males with SSc, age 50.8±13.0 years, disease duration 6.2±6.0 years; 24 with diffuse cutaneous SSc (dcSSc) and 38 with limited cutaneous SSc (lSSc). The DHI had a mean±SD score of 22.8±19.5, range 0–71 (with possible range 0–90) at baseline, and 24.3±21.1, range 0–73 at follow-up. The DHI presented an excellent test-retest reliability (ICC 0.98), a good internal consistency (Cronbach's alpha 0.960). Criterion validity of the DHI was proved by moderate to strong correlations with HAMIS, FE, FTP, Δ FTP and the SHAQ disability index (Spearman rho 0.57–0.85, p<0.001). The discriminative capacity of the DHI was proven by statistically significant differences between patients with and without: synovitis, flexion contractures of the fingers, and history of DUs. The sensitivity to change (ES of 0.27 and SRM of 0.52) was acceptable for detecting the minimally important difference. Conclusions: The DHI is a reliable, valid and easy to apply tool for hand involvement assessment in patients with SSc. The preliminary results on sensitivity to change suggest DHI could be a sensitive measure to detect change in clinical status, however more early diffuse SSc patients are needed to confirm these findings. Acknowledgement: * This abstract was realized as part of the "Development of a computer-based nailfold videocapillaroscopy (NVC) system for longitudinal evaluation of patients with systemic sclerosis" (QUANTICAP) project, financed by the UEFIS-CDI PN-II-PT-PCCA-2013–4-1589 grant. Disclosure of Interest: None declared